The Concept of Survival in August Strindberg’s A Dream Play - Awad Ibrahim, Ghassan (Opción, 2019)
The Swedish well-known playwright August Strindberg (1849-1912) deals with the concept of survival of mankind in his masterpiece A Dream Play through suffering due to the difficult circumstances people worldwide face during their lifetime so that they finally can get relief. When writing A Dream Play, Strindberg was not acquainted with Sigmund Freud’s conception of dreams but Freud as a specialist in the psychoanalysis is required for inter- preting the real nature and structure of the play. For Freud, dreams which stem from the human subconscious are so significant in affecting and forming the individual personality and they also have the power to depict the manners and inclinations of the human being. In his play, Strindberg presents real tormented characters taken from almost all walks of life, striving for survival in spite of their problematic circumstances. In a Freudian sense, the play is considered a fulfillment of a wish that all people in the world should cast off their servitude to their illusions so that the spiritual values can be prevailed through increasing and improving of people thoughts and consciousness. Re- ally the play is a call for mankind to go back to spiritual values such as love, peace, righteousness, truth and forgiveness in order to achieve peace of mind in this mortal world and in the hereafter.